THE POTENTIAL ENERGY OF GEL POLYMER ELECTROLYTES FROM GUPPY (Poecilia reticulata) FISH WASTE FOR BATTERY APPLICATION - Zakaria, Khaulah; Nik Ali, Nik Aziz (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
This study aims to determine the potential energy of gel polymer electrolytes from guppy (Poecilia reticulata) fish waste for battery applications through different parameters. The parameters include the number of fish, the number of days, and the battery’s longevity. This experiment is underpinned by the concept of an electrical energy storage system of gel polymer electrolytes and urea as an energy carrier. The ammonia secreted by fish contains NH4+ which has positive hydrogen ion. The hydrogen ion in this element has the ability to produce electricity. This experiment involved tests on different batches of fish, with 5,10 and 15 fish in each respective batch. The wastewater samples were taken every two days, made into gel polymer electrolytes using agar, and inserted into the battery. The output voltage was recorded using a voltmeter, and each battery showed an increasing pattern of voltmeter reading against the number of days. For example, the highest voltage output was produced by a battery that used the wastewater sample with 15 fish on the 10th day, resulting in 0.45V. This is due to an increase of the amount of ammonia accumulated from fish waste within that 10 days. Batteries with the highest outputs of voltage from respective of number of fish were then taken for longevity test. The two weeks tests showed gradual decrease in the result due to many factors, including the ionic transference number and the disassociation of ionic particles in the electrolytes. The estimation of the battery longevity from water samples with 5, 10, and 15 fish were 71.47 days, 27.82 days and 34.44 days, respectively. This study proves that the gel polymer electrolytes from guppy, Poecilia reticulata has the potential to be used in batteries as an energy source.